The Effect of Return On Equity (ROE), Debt Equity Ratio (DER), and Earning Per Share (EPS) on Share Prices in LQ45 Indexed Companies on the Indonesia Stock Exchange for the 2015 - 2018 Period - Sulistyanie, Astin; Bayu Aji Sumantri, Muhammad (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The LQ45 is a stock market index on the Indonesia Stock Exchange (IDX) which consists of 45 companies that meet certain criteria. The LQ45 index consists of the 45 most liquid stocks (the name LQ refers to Liquid) and was introduced in February 1997. LQ45 covers 70% of the capitalization value and transactions in the Indonesian Stock Market. The number of population for this research is 45 companies and the number of sample that examined after passed the purposive sampling phase is 29 companies.This research is aimed to test the effect of Return On Equity (ROE), Debt to Equity Ratio (DER), and Earning Per Share (EPS) on Stock Price in LQ45 companies in Indonesia Stock Exchange from 2015 to 2018. The method used in this research are descriptive and verification method with quantitative analysis. The population in this study is the LQ45 companies registered in IDX. Analysis of data used Fixed Effect Model from panel data regression analysis. The results showed that the variable Debt to Equity Ratio (DER) and Return On Equity (ROE) had no significant effect on stock prices. Meanwhile, Earnings per Share (EPS) has a positive and significant effect on stock prices on the LQ45 index. The results of this study are expected that the variable Return on Assets (ROE), Debt to Equity Ratio (DER), and Earnings per Share (EPS) can be used as a reference, both by company management and by investors in determining investment strategies.